Journal of technical education seience (Ho Chi Minh city University of Technology and Education, 2018)
Contents: A simulation study on performance characteristics of simulated biogas engine with high compression ratio; hierarchical sliding mode control for an underactuated mimo system; visual servoing for monitoring and diagnosing in farming; analysis mixed-mode fracture toughness (mode I/II) of a single layer graphene sheet by finite element methods simulation,...